2015
DOI: 10.2166/wcc.2015.044
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis in climatic variables and impacts on rice yield in Nigeria

Abstract: The effects of changes in meteorological parameters on rice yield variations were considered. Weather parameters, temperature (T), rainfall (R), relative humidity (RH) and solar radiation (SR), and rice yield variation for Ibadan were analyzed. Meteorological parameters were obtained from the International Institute for Tropical Agriculture while rice yield data were obtained from the Africa Rice Centre both in Nigeria for three decades (1980–2010). Trends analysis of past and recent variations using the weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The null and alternative hypothesis are expressed by H 0 is the variable data is homogenous; and H a is the variable is heterogeneous and there is a date at which there is a change in data. Akinbile et al (2015) and Koudahe et al (2017) reported that Mann-Kendall test a nonparametric method for trend analysis and used for analyzing temporal trends in annual monthly rainfall, ET o , and aridity index, and a very useful tool in climatology and hydrology time series. Some of the advantages of using this test are that being a nonparametric test, it does not require the data to be normally distributed and the test has low sensitivity to abrupt breaks due to inhomogeneous time F I G U R E 1 Six cities, one in each agro-ecological zone considered for the study series (Koudahe et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The null and alternative hypothesis are expressed by H 0 is the variable data is homogenous; and H a is the variable is heterogeneous and there is a date at which there is a change in data. Akinbile et al (2015) and Koudahe et al (2017) reported that Mann-Kendall test a nonparametric method for trend analysis and used for analyzing temporal trends in annual monthly rainfall, ET o , and aridity index, and a very useful tool in climatology and hydrology time series. Some of the advantages of using this test are that being a nonparametric test, it does not require the data to be normally distributed and the test has low sensitivity to abrupt breaks due to inhomogeneous time F I G U R E 1 Six cities, one in each agro-ecological zone considered for the study series (Koudahe et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Akinbile et al () and Koudahe et al () reported that Mann–Kendall test a nonparametric method for trend analysis and used for analyzing temporal trends in annual monthly rainfall, ET o , and aridity index, and a very useful tool in climatology and hydrology time series. Some of the advantages of using this test are that being a nonparametric test, it does not require the data to be normally distributed and the test has low sensitivity to abrupt breaks due to inhomogeneous time series (Koudahe et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlenker and Roberts (2009a, b) found that temperature was positively correlated with crop yield in a suitable temperature range in America. Akinbile et al (2015) analyzed the influence of climate change on rice yield in Nigeria and found that temperature had significant positive effects on rice yield. In China, Tao et al (2008) found that the temperature significantly increased with rice yield in China during 1951-2002, especially in northeastern China.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in temperature will increase the frequency of extreme weather events, especially extreme high temperature events. Rice is among the world's most important food crops, and it is a primary source of food for over 50% of the world's population [2,3]. Frequent and extreme high temperature events will increase the risk of rice yield losses [4], which is a serious threat to the global food supply.…”
Section: Introductionmentioning
confidence: 99%